"Axitinib Affects Cell Viability and Migration of a Primary Foetal Lung Adenocarcinoma Culture". (2nd January 2014) - Menna, Cecilia; De Falco, Elena; Pacini, Luca; Scafetta, Gaia; Ruggieri, Paola; Puca, Rosa; Petrozza, Vincenzo; Ciccone, Anna Maria; Rendina, Erino Angelo; Calogero, Antonella; Ibrahim, Mohsen
<x xml:space="preserve">Abstract</x> Fetal lung adenocarcinoma (FLAC) is a rare variant of lung adenocarcinoma. Studies regarding FLAC have been based only on histopathological observations, thus representative in vitro models of FLAC cultures are unavailable. We have established and characterized a human primary FLAC cell culture, exploring its biology, chemosensitivity, and migration. FLAC cells and specimen showed significant upregulation of VEGF165 and HIF-1α mRNA levels. This observation was confirmed by in vitro chemosensitivity and migration assay, showing that only Axitinib was comparable to Cisplatin treatment. We provide a suitable in vitro model to further investigate the nature of this rare type of cancer.